SETTING UP AN INDUSTRIAL CONTROL SYSTEMS LABORATORY - Liuwan, Haryanto Natalius; Schellekens, Casper; Trivellato, Daniel (Jurnal Informatika, 2014)
With the evolution of Industrial Control Systems, many solutions from vendors are offered for industries. But sadly, most of those solutions are close-sourced, delivering lack of support for third parties who aim to develop Industrial Control Systems further. A start-up company named SecurityMatters needs an industrial instrument to simulate industrial environment to have a better idea how a particular protocol works. The application made in this project was developed using Java programming language to have compatibilities across platforms. An Object-Oriented-Programming and Model-View-Controller pattern are used as well to ensure maintainability. This application can be used to demonstrate capabilities of Modbus protocol and test industrial devices for vulnerabilities.